Accuracy of delirium risk factors in adult intensive care unit patients - Luciana Aparecida Costa Carvalho; Marisa Dibbern Lopes Correia; Ráisa Camilo Ferreira; Micnéias Lacerda Botelho; Elaine Ribeiro; Erika Christiane Marocco Duran (SciELO, 2022)
Abstract Objective: To assess the accuracy measurements for predisposing and precipitating Risk Factors for delirium in an adult Intensive Care Unit. Method: Cohort, prospective study with patients over 18 who had been hospitalized for over 24 hours and were able to communicate. The patients were assessed once a day until the onset of delirium or permanence in the Intensive Care Unit. Instruments were employed to track delirium, characterize the sample, and identify the risk factors. Descriptive statistics was employed for sample characterization and accuracy tests for risk factors. Results: The included patients amounted to 102, 31 of which presented delirium. The predisposing predictive risk factors were hypoalbuminemia, American Society of Anesthesiology over three, severity, altered tissue perfusion, dehydration, and being a male, whereas precipitating predictive factors were physical restraint, infection, pharmacological agent, polypharmacy, anemia, altered renal function, dehydration, invasive devices, altered tissue perfusion and altered quality and quantity of sleep. Conclusion: An accurate identification of predisposing and precipitating risk factors may contribute to planning preventive measures against delirium.